Red cell folate concentrations in patients with Crohn's disease on parenteral nutrition. Issue 769 (November 1989) - Tominaga, M.; Iida, M.; Aoyagi, K.; Kohrogi, N.; Matsui, T.; Fujishima, M.
Abstract : To examine changes in the folate concentrations in red cell during relatively long-term total parenteral nutrition (TPN), 10 Japanese patients with Crohn's disease (7 males), the mean Crohn's disease activity index on admission being 211, were given folic acid in a dose of 400 micrograms/day (AMA-FDA formulation) or 800 micrograms/day for 6-16 weeks (mean 10.5). The red cell folate concentrations were determined before TPN and once every week or 2-4 weeks thereafter. The folate concentrations were very low even after TPN with folic acid of 400 micrograms/day. In those given 800 micrograms of daily folic acid, the folate levels tended to increase, but did not reach the normal range. We propose that folic acid over 800 micrograms/day or a double dose of AMA-FDA formulation should be prescribed for Crohn's disease treated with long-term TPN.